(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe main question raised in this paper is: Is it possible to translate the ‘genre’of Quran? And if this ‘genre’ is Quran specific, a ‘genre’ of its own, i.e. a unique one,how can the Quranic text be translated from Arabic into English or any otherlanguage? This question has been raising a lot of controversy among translationtheorists, linguists, philosophers and scholars of Islam and specialists in the sciencesof Arabic language let alone Quran exegetes. Scholars of the Arabic language andscholars of Islam have argued that because of the genre of Quran is the genre of (ijaz),translatability can never be possible. Equivalence, thus, cannot be achieved especiallyif we know that so far there has been no unanimous definition of the term.Therefore, what translators of the Quranic text are involved with is transferringmeaning of the Quranic text. But meaning (content) is encapsulated in the Formwhich is distinctly and uniquely rhetorical in Quran. In other words, such aninextricable content-form relationship should make the process of transferringmeaning not an easy one at all, especially as we know that the Quranic text is sacredand sensitive.Thus, the periphrastic way which has already been put forward by Raof(2001: 6) can be seen as a convenient solution to achieve a degree of approximationbetween the source text and the target text.Having supported the notion of approximation, I opted to choose certainverses with certain syntactic and lexical aspects from the Quran. The point is tocompare three versions of translations of each verse to see which version is mostapproximate to the Quranic text of the verse. The three versions are by AbdullahYusuf Ali (non Arab Moslem), Marmaduke Pickthall ( a British national whoconverted to Islam) and Ahl-lul-Bait institution ( a Moslem Assembly with Arabic asmother tongue).To support my argument, I relied on Al-Mezan Fi-Tafseer Al-Quran (Al-Mezan Exegesis) by the Moslem scholar Mohammed Hussein Tabatabae (2006) andthe authentic monolingual Arabic Dictionary Lisan Al-Arab (Ibn Manzur: 2005 ed.4).One main conclusion made in this paper is that the task of translating the meaning ofQuran cannot be rightfully carried out by translators on individual basis. Rather, itmust be institutionalized. There is a need for setting up a special institution entrustedwith such a meticulous job.